Perovskite single crystal photodetector based on electrode / transport layer composite film
By using Ti3C2TX-TiO2 composite film and in-situ grown Ti3C2TX electrode structure in perovskite photodetectors, the defects of increased interfaces and halogen ion migration in traditional perovskite photoelectric devices are solved, and higher device performance and stability are achieved, and the self-drive effect is provided.
Patent Information
- Application Number
- CN202411675915.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-22
AI Technical Summary
In traditional perovskite optoelectronic devices, the interface between the electrode and the transport layer increases defects, hinders the transmission of carriers and affects device performance. In addition, the halogen ions in perovskite materials migrate under the action of an external electric field and react with the metal electrode, causing dark current drift and affecting device stability.
Using the structure based on the electrode/transport layer composite film, the composite film is formed by oxidizing Ti3C2TX and TiO2, the interface between the electrode and the transport layer is eliminated, and the Ti3C2TX electrode is grown in situ on the perovskite single crystal to form a detector structure of Ti3C2TX-TiO2/perovskite/Ti3C2TX.
This structure reduces obstacles in carrier transport, improves device performance, and avoids the reaction between perovskites and metal electrodes, enhancing device stability. In addition, the perovskite layer and the TiO2 layer form a PN junction, creating a built-in electric field, allowing the device to respond to light under unbiased conditions and have a self-driving effect.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new perovskite single crystal materials and perovskite single crystal optoelectronic devices, and in particular relates to a perovskite photodetector based on an electrode / transmission layer composite film and a preparation method thereof. Background Art
[0002] In recent years, perovskite materials have become a hot research direction in the field of optoelectronic devices, among which organic-inorganic hybrid perovskite materials are particularly popular. As an emerging semiconductor material, it has many excellent properties, such as direct and adjustable band gap, high absorption coefficient and absorption band covering ultraviolet to near-infrared band, high carrier mobility and relatively balanced electron and hole transport properties.
[0003] At present, polycrystalline thin-film perovskite optoelectronic devices usually have a structure of electrode-transport layer-perovskite layer-transport layer-electrode. However, in this case, there will be an interface between the transport layer and the electrode, and the existence of the interface will increase defects and hinder the transmission of carriers, ultimately affecting the performance of the device. For perovskite single-crystal optoelectronic devices with good stability, they generally form a metal-semiconductor-metal structure with metals. When such devices are in working state, the halogen ions in the perovskite material will migrate over a large range through the defects and grain boundaries in the material under the action of an external electric field, and then react with the metal electrode, causing dark current drift, affecting the performance and stability of the device. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a perovskite photodetector based on an electrode / transport layer composite film, in which there is no interface between the detector electrode and the transmission layer, and overcomes the disadvantage of the traditional perovskite detector that the metal electrode reacts with the perovskite material. Specifically, the present invention adopts the following technical solutions:
[0005] On the one hand, the present invention provides a perovskite single crystal photodetector based on an electrode / transport layer composite film, which comprises an electrode / transport layer composite film located at a lower layer, a perovskite single crystal located at a middle layer, and a Ti3C2T X Electrode; the electrode / transport layer composite film is Ti3C2T X -TiO2 composite film, the perovskite single crystal is in-situ grown on the Ti3C2T X -TiO2 composite film.
[0006] For the above-mentioned perovskite single crystal photodetector, preferably, the Ti3C2T X -TiO2 composite film is made by X The film is oxidized to form a dense layer of TiO2 on the surface, including Ti3C2TX as electrodes, and TiO2 as transport layer.
[0007] For the above-mentioned perovskite single crystal photodetector, preferably, the oxidation treatment is natural oxidation treatment, plasma etching treatment, or inert gas high temperature annealing treatment.
[0008] Among them, for the oxidation treatment described above, preferably, the plasma etching treatment can be oxygen plasma etching, specifically the following method: Ti3C2T X The film was placed in a plasma etcher, high-purity O2 was introduced, and etching was performed for 30-60 min under the conditions of a plasma etcher working power of 20-30 W and an internal pressure of 30-50 Pa to obtain Ti3C2T with the surface oxidized to TiO2. X -TiO2 composite thin film.
[0009] Among them, for the above-mentioned natural oxidation treatment, the preferred method is: X The film was placed in an electronic constant temperature drying oven at a humidity of 10% to 15% and a temperature of 25°C for 1 to 3 months. The film after being taken out was Ti3C2T with the surface oxidized to TiO2. X -TiO2 composite thin film.
[0010] Among them, for the above-mentioned high temperature inert gas annealing treatment, the preferred method is: X The film was placed in a tube furnace, the temperature was set to rise at 5-10°C / min, the temperature was maintained at 400-800°C, the holding time was 0.5-1h, the temperature was lowered at 5-10°C / min, and high-purity argon was introduced at the same time. The surface functional groups reacted at high temperature and finally Ti3C2T with TiO2 on the surface was obtained. X -TiO2 composite thin film.
[0011] For the above-mentioned perovskite single crystal photodetector, preferably, the perovskite single crystal is MAPbBr Y I 3-Y Single crystal, wherein 0≤Y≤3. Preferably, Y is 0, 1, 2 or 3.
[0012] For the above-mentioned perovskite single crystal photodetector, preferably, the Ti3C2T X -TiO2 composite film thickness is 0.1~0.5 mm, the upper layer of Ti3C2T X The electrode thickness is 0.1~0.5 mm, and the perovskite single crystal thickness is 1~10 mm.
[0013] On the other hand, the present invention also provides a method for preparing the perovskite single crystal photodetector, which comprises first preparing Ti3C2T X -TiO2 composite film, then on Ti3C2T X -TiO2 composite film in situ growth of perovskite single crystals, and then preparation of Ti3C2T on the perovskite single crystals X electrode.
[0014] For the above-mentioned preparation method, preferably, the preparation of Ti3C2T X -TiO2 composite films including Ti3C2T X Preparation of aqueous solution, Ti3C2T X The thin film was then oxidized to make Ti3C2T X TiO2 is generated on the film surface to obtain Ti3C2T X -TiO2 composite thin film.
[0015] Preferably, Ti3C2T is prepared X -TiO2 composite film, one method that can be used is:
[0016] Take Ti3C2T X The aqueous solution is placed in a suction filtration funnel. After the solution is filtered and fixed, it is transferred to a vacuum drying oven for drying. X The film was peeled off from the filter paper and oxidized to form dense TiO2 in situ on its surface.
[0017] For the above-mentioned preparation method, preferably, the evaporation crystallization method is used to prepare Ti3C2T X MAPbBr grown on TiO2 composite film Y I 3-Y Single crystal, wherein 0≤Y≤3. Exemplarily, Y is 0, 1, 2 or 3.
[0018] Preferably, the evaporation crystallization method is used to form Ti3C2T X Growth of MAPbBr on TiO2 composite films Y I 3-Y Single crystal, where 0≤Y≤3. Exemplarily, Y is 0, 1, 2 or 3. Taking MAPbI3 as an example, one method that can be used is: weigh MAI and PbI2 powders with a molar ratio of 1:1 and add them to a gamma-butyrolactone (GBL) solution to prepare a MAPbI3 precursor solution with a concentration of 1-1.5 mol / L; place the composite film in the MAPbI3 precursor solution, grow a perovskite single crystal by evaporation crystallization, and after the single crystal grows to a particle size of 1-10 mm, place Ti3C2T XThe film and the MAPbI3 single crystal on the film were taken out from the solution and placed in a vacuum oven and dried at 70°C for 1-2 h to obtain a Ti3C2T X -MAPbI3 single crystals grown in situ on TiO2 composite film.
[0019] For the above-mentioned preparation method, preferably, the preparation of Ti3C2T X The electrode is made by centrifugation of Ti3C2T X The aqueous solution is concentrated into a high-concentration slurry, which is then scraped onto the surface of the perovskite layer and dried.
[0020] As a more preferred solution, the preparation of Ti3C2T X The electrode may be provided by a method comprising the following steps:
[0021] (1) Add Ti3C2T to a concentration of 10 mg / ml X An equal amount of N,N-dimethylformamide (DMF) was added to the aqueous solution, and the water and Ti3C2T X Layering;
[0022] (2) Take the bottom black Ti3C2T X The precipitate is added with DMF again, and the residual water is separated by centrifugation. This step is repeated 2-4 times;
[0023] (3) Take the precipitate obtained in step (2) and add ethyl acetate solution to make a Ti3C2T3O4 solution with a concentration of 20-30 mg / ml. X Slurry; Due to Ti3C2T X Aqueous solution will hydrolyze the perovskite, while ethyl acetate will not react with the perovskite;
[0024] (4) Ti3C2T X The slurry is scraped on the surface of the perovskite layer and dried to obtain Ti3C2T X electrode.
[0025] As a specific preferred embodiment, the method for preparing a perovskite photodetector based on an electrode / transport layer composite film of the present invention may include the following steps:
[0026] (1) Production based on Ti3C2T X Ti3C2T for electrodes / TiO2 transport layers X -TiO2 composite film;
[0027] (2) Ti3C2T X The aqueous solution is concentrated into a high concentration slurry to prepare Ti3C2T X electrode;
[0028] (3) In situ growth of MAPbBr on the composite film prepared in (1) was performed by evaporation crystallization. Y I 3-Y (Y = 0,1,2,3) single crystals. The evaporation crystallization method is to reduce the MAPbBr by heating and evaporating the solvent. Y I 3-Y The solubility of MAPbBr in solution Y I 3-Y Crystals precipitated from the solution.
[0029] (4) In MAPbBr Y I 3-Y Ti3C2T prepared by single crystal surface scraping step (2) X The slurry is dried in a vacuum oven to form Ti3C2T X The electrode is Ti3C2T X -TiO2 / Perovskite / Ti3C2T X Detector.
[0030] The perovskite-based photodetector of the present invention has a Ti3C2T X The film is etched with oxygen ions, naturally oxidized, and annealed in high-temperature inert gas to form dense TiO2 on the surface, which forms a surface transmission layer of TiO2 and a bottom layer of Ti3C2T X Ti3C2T electrode X -TiO2 composite film structure, by using suitable perovskite materials on the film and scraping Ti3C2T on top of the perovskite X Electrode, prepared structure is Ti3C2T X -TiO2 / Perovskite / Ti3C2T X The photodetector not only solves the problem that the appearance of the above-mentioned interface affects the performance and the reaction between perovskite and metal electrodes affects the stability of the device, but also can form a built-in electric field inside the device, so that the device can achieve a self-driving effect.
[0031] The present invention is a perovskite single crystal photodetector based on an electrode / transport layer composite film. Since there is no interface between the detector electrode and the transport layer, there are few obstacles encountered in the carrier transport process, so the detector performance is good. The present invention overcomes the shortcomings of the traditional perovskite detector metal electrode and the halogen ion migration in the perovskite material to react, and improves the stability of the device. In addition, in the present invention, the perovskite layer and the TiO2 layer form a PN junction to generate a built-in electric field, and the photogenerated carriers can be separated under bias conditions, so the device has a fast response speed and has a self-driving effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The structure of the perovskite detector based on the electrode / transport layer composite film; 1 and 2 are superimposed to form a composite film structure, 1 is Ti3C2T X Electrode, 2 is TiO2 transport layer; 3 is MAPbBr Y I 3-Y Single crystal, 4 is high concentration Ti3C2T X Ti3C2T made from slurry X electrode.
[0033] Figure 2 The untreated Ti3C2T prepared in Example 1 X Scanning electron microscopy image of the film.
[0034] Figure 3 The untreated Ti3C2T prepared in Example 1 X X-ray diffraction pattern of the film.
[0035] Figure 4 The Ti3C2T3 obtained by oxygen plasma etching in Example 1 X -Scanning electron microscope image of TiO2 composite film.
[0036] Figure 5 The Ti3C2T3 obtained by oxygen plasma etching in Example 1 X -X-ray diffraction pattern of TiO2 composite film.
[0037] Figure 6 This is the current-time curve of the MAPbI3 single crystal perovskite photodetector prepared in Example 1 after long-term storage.
[0038] Figure 7 In Example 1, Ti3C2T was obtained by etching with oxygen plasma. X Current-voltage curve of MAPbI3 single crystal perovskite photodetector prepared with -TiO2 composite film as substrate under 480nm wavelength light.
[0039] Figure 8 In Example 1, Ti3C2T was obtained by etching with oxygen plasma. X Time-current curve of MAPbI3 single crystal perovskite photodetector prepared with -TiO2 composite film as substrate under 0V bias at 480 nm wavelength.
[0040] Fig. 9 In Example 2, Ti3C2T was obtained by etching with oxygen plasma. X Current-voltage curve of MAPbBr3 single crystal perovskite photodetector prepared with -TiO2 composite film as substrate under 480 nm wavelength light.
[0041] Fig.10 In Example 2, Ti3C2T was obtained by etching with oxygen plasma. X -The current-time curve of the MAPbBr3 single crystal perovskite photodetector prepared with TiO2 composite film as the substrate under 0V bias at 480 nm wavelength.
[0042] Fig.11 Example 3 is Ti3C2T obtained by high temperature annealing with inert gas X Current-voltage curve of MAPbBr3 single crystal perovskite photodetector prepared with -TiO2 composite film as substrate at 480 nm wavelength.
[0043] Fig.12 Example 3 is Ti3C2T obtained by high temperature annealing with inert gas X Time-current curve of MAPbBr3 single crystal perovskite photodetector prepared with -TiO2 composite film as substrate under 0V bias at 480 nm wavelength.
[0044] Fig.13 Example 4 is to obtain Ti3C2T by natural oxidation X Current-voltage curve of MAPbI3 single crystal perovskite photodetector prepared with -TiO2 composite film as substrate at a wavelength of 480 nm.
[0045] Fig.14 Example 4 is to obtain Ti3C2T by natural oxidation X Time-current curve of MAPbI3 single crystal perovskite photodetector prepared with -TiO2 composite film as substrate under 0V bias at 480 nm wavelength.
[0046] Fig.15 In Example 5, Ti3C2T was obtained by etching with oxygen plasma. X Current-voltage curve of MAPbBrI2 single crystal perovskite photodetector prepared on the substrate of -TiO2 composite film at a wavelength of 480 nm.
[0047] Fig.16 In Example 5, Ti3C2T was obtained by etching with oxygen plasma. X Time-current curve of MAPbBrI2 single crystal perovskite photodetector prepared on the substrate of -TiO2 composite film under 0V bias at 480 nm wavelength.
[0048] Fig.17 Comparative Example 1 is made of untreated Ti3C2T X -The current-voltage curve of MAPbI3 single crystal perovskite photodetector prepared with TiO2 film as substrate under 480nm wavelength light.
[0049] Fig.18 Comparative Example 1 is made of untreated Ti3C2T X -Time-current curve of MAPbI3 single crystal perovskite photodetector prepared on TiO2 film as substrate under 0V bias of 480nm wavelength light. DETAILED DESCRIPTION
[0050] The following embodiments are further descriptions of the content of the present invention as an explanation of the technical content of the present invention, but the essential content of the present invention is not limited to the following embodiments. Ordinary technicians in this field can and should know that any simple changes or replacements based on the essential spirit of the present invention should fall within the scope of protection required by the present invention.
[0051] Example 1
[0052] A method for preparing a perovskite detector based on an electrode / transport layer composite film comprises the following steps:
[0053] (1) Ti3C2T X -Preparation of TiO2 composite thin films
[0054] (1a) Measure 15 mL of hydrochloric acid and 5 mL of deionized water (DI), mix and stir for 5 min, add 1 g of LiF and stir for 3 min, react for 10 min, weigh 1 g of titanium aluminum carbide (Ti3AlC2) raw material and divide it into 10 equal parts. After the reaction of LiF is completed, add one part of the raw material every 3 min. After the last part is added, continue to stir for 10 min. After the stirring is completed, put it in a water bath at 35 ° C and continue to react for 24 h;
[0055] The liquid after the reaction was completed was transferred to a centrifuge tube, 50 ml of deionized water was added, and the mixture was centrifuged at 3500 rpm for 5 min. The supernatant was removed, 50 ml of deionized water was added again and the mixture was shaken. The centrifugation was repeated until the pH value of the supernatant was close to neutral. The shaken liquid was poured into a ventilation bottle for ultrasonic ventilation (argon for 1 h), and the ultrasonic temperature was below 35 °C. The liquid after ultrasonication was taken out and centrifuged once (3500 rpm for 5 min), and the supernatant was taken out. The remaining was Ti3C2T X Then put it into a certain amount of deionized water and shake it thoroughly to obtain 10 mg / ml Ti3C2T X Aqueous solution;
[0056] Take Ti3C2T with a concentration of 10 mg / ml X A total of 5 ml of the aqueous solution was placed in a suction filtration funnel. After the solution was filtered and fixed, it was transferred to a 40°C vacuum drying oven and dried for 1 h to remove the filter membrane and Ti3C2T XThin film separation to obtain Ti3C2T with a thickness of 0.5 mm X Thin films, such as Figure 2 Untreated Ti3C2T X Scanning electron microscope image of thin film, Figure 3 Shown is untreated Ti3C2T X X-ray diffraction pattern of the film.
[0057] (1b) Ti3C2T X The film was placed in a plasma etcher, high-purity O2 was introduced, and the plasma etcher was etched for 60 minutes at a working power of 20W and an internal pressure of 50Pa to obtain Ti3C2T with the surface oxidized to TiO2. X -TiO2 composite films, such as Figure 4 The picture shows Ti3C2T after etching. X -Electron microscope scanning image of TiO2 composite film, Figure 5 The Ti3C2T obtained by etching is shown in Figure 2. X -X-ray diffraction pattern of TiO2 composite film. Figure 2 and Figure 4 It can be seen that after oxygen etching, Ti3C2T X Many small white particles appear on the surface of the film. Figure 3 and Figure 5 In contrast, Ti3C2T X Ti3C2T on the film surface X The diffraction peak gradually weakened and the diffraction peak of TiO2 appeared, which can prove that Ti3C2T X The film produces TiO2, which is then etched to form Ti3C2T X -TiO2 composite thin film.
[0058] (2) Ti3C2T X Preparation of high concentration slurry
[0059] Take Ti3C2T with a concentration of 10 mg / ml X Add an equal amount of DMF to 50 ml of the aqueous solution, place the centrifuge tube containing the mixed solution into a centrifuge at 8000 rpm for 15 min, pour out the upper solution and leave the precipitate.
[0060] Pour DMF into the precipitate again and put the centrifuge tube containing the solution into the centrifuge at 8000 rpm for 15 min. Pour out the upper solution and leave the precipitate. Repeat this operation three times to obtain a certain amount of precipitate. Add a certain amount of ethyl acetate solution to prepare a high concentration of Ti3C2T X Slurry, prepared with high concentration of Ti3C2T XThe slurry concentration was 25 mg / ml.
[0061] (3) Preparation of MAPbI3 single crystals
[0062] Use a balance to weigh 0.413 g of MAI and 1.199 g of PbI2 (1:1 molar ratio) in a 20 ml sample bottle, dissolve them in 2 ml of GBL (gamma-butyrolactone) to obtain a MAPbI3 solution with a concentration of 1.3 mol / L, and then stir on a hot plate at 60 °C for 4 h until the drug is completely dissolved.
[0063] The Ti3C2T X -TiO2 composite film was placed in the prepared MAPbI3 solution, and then allowed to stand at 110°C for 4 hours to obtain MAPbI3 single crystals with a thickness of 1 mm grown in situ on the composite film. The film was taken out of the solution, placed in a vacuum oven, and dried at 70°C for 2 hours to obtain MAPbI3 single crystals grown in situ on the composite film.
[0064] (4) Ti3C2T X Preparation of electrodes
[0065] Take an appropriate amount of Ti3C2T prepared in step (2) X The slurry is evenly applied on the MAPbI3 single crystal obtained in step (3), and the coated Ti3C2T X The MAPbI3 single crystal was placed in a vacuum oven and allowed to stand at 25 °C for 3 h to obtain a dry Ti3C2T X electrode.
[0066] (5) Testing
[0067] Place the sample on the probe station with the upper electrode Figure 1 The Ti3C2T X , the lower electrode is Figure 1 The electrode indicated by 1 in the figure is scanned with voltage on the upper and lower electrodes to obtain the dark current and the photocurrent under 480nm light, as shown in Figure 6 As shown, by comparing the dark current with the voltage corresponding to the bottom peak of the photocurrent, the open circuit voltage of the device shifts to the right, thus proving the existence of a built-in electric field in the device.
[0068] When the applied voltage is 0V, the time-current curve under periodic optical switch illumination is as follows: Figure 7 As shown in the figure, the device has good performance through its standard square wave shape. The device was placed in a constant temperature electronic drying oven for 2 months and its 1000s time-current curve was tested, as shown in the figure below. Figure 8 As shown, it can be seen that the attenuation of the curve is small, which proves that it has good stability.
[0069] Example 2
[0070] (1) Ti3C2T X -The preparation of TiO2 composite film is the same as in Example 1.
[0071] (2) Ti3C2T X The preparation of high concentration slurry is the same as in Example 1.
[0072] (3) Preparation of MAPbBr3 single crystal, the steps are as follows:
[0073] Use a balance to weigh 0.224 g of MAI and 0.734 g of PbI2 (1:1 molar ratio) in a 20 ml sample bottle, dissolve them in 2 ml of DMSO (dimethyl sulfoxide) to obtain a MAPbBr3 solution with a concentration of 1.0 mol / L, and then stir on a hot plate at 60 °C for 4 h until the drugs are completely dissolved.
[0074] In step (1), Ti3C2T X -TiO2 composite film was placed in the prepared solution, and then allowed to stand at 75°C for 4 h to obtain MAPbBr3 single crystals with a thickness of 0.6 mm grown in situ on the composite film. The film was taken out of the solution and placed in a vacuum oven and dried at 60°C for 2 h to obtain Ti3C2T X -MAPbBr3 single crystals grown in situ on TiO2 composite film.
[0075] (4) Ti3C2T X Preparation of electrodes
[0076] Take an appropriate amount of Ti3C2T prepared in step (2) X The slurry is evenly applied on the MAPbBr3 single crystal obtained in step (3), and the coated Ti3C2T X The MAPbBr3 single crystal was placed in a vacuum oven and allowed to stand at 25 °C for 3 h to obtain a dry Ti3C2T X electrode.
[0077] (5) Testing
[0078] Place the sample on the probe station with the upper electrode Figure 1 The Ti3C2T X , the lower electrode is Figure 1 The electrode indicated by 1 in the figure is scanned with voltage on the upper and lower electrodes to obtain the dark current and the photocurrent under 480nm light, as shown in Fig. 9 As shown in the figure, by comparing the dark current with the voltage corresponding to the bottom peak of the photocurrent, the open circuit voltage of the device shifts to the right, thus proving that the device has a built-in electric field. When the external voltage is 0V, the time-current curve under periodic light switch illumination is as follows Fig.10 As shown, a relatively complete square wave is presented, which proves that the device has good performance.
[0079] Example 3
[0080] (1) Ti3C2T X -Preparation of TiO2 composite thin films
[0081] (1a)Ti3C2T X The preparation of the film is the same as in Example 1.
[0082] (1b) Ti3C2T X The film was placed in a tube furnace, the rising temperature was set at 5°C / min, the holding temperature was set at 400°C, the holding time was set at 1 h, the falling temperature was set at 10°C / min, and high-purity argon was introduced at the same time. After the furnace temperature dropped to room temperature, the film was taken out to obtain a Ti3C2T3O3 film with a thickness of 0.5 mm. X -TiO2 composite thin film.
[0083] (2) Ti3C2T X The preparation of high concentration slurry is the same as in Example 1.
[0084] (3) The preparation of MAPbI3 single crystal is the same as that in Example 1.
[0085] (4) Ti3C2T X The preparation of the electrode is the same as in Example 1.
[0086] (5) Testing
[0087] Place the sample on the probe station with the upper electrode Figure 1 The Ti3C2T X , the lower electrode is Figure 1 The electrodes indicated by 4 in the figure are scanned with voltages applied to the upper and lower electrodes to obtain dark current and photocurrent under 480nm illumination, as shown in Fig.11 As shown in the figure, it can be seen that the peak from dark current to photocurrent gradually shifts to the left, so there is a built-in electric field inside the device; when the external voltage is 0V and the wavelength is 480nm, the time-current curve under the periodic optical switch is as follows Fig.12 As shown, a relatively complete square wave is presented, which proves that the device has good performance.
[0088] Example 4
[0089] (1) Ti3C2T X -Preparation of TiO2 composite thin films
[0090] (1a) Ti3C2T X The preparation of the film is the same as in Example 1.
[0091] (1b) Ti3C2T X The film was placed in an electronic constant temperature drying oven at a humidity of 15% and a temperature of 25°C for 3 months. The film after being taken out was Ti3C2T with the surface oxidized to TiO2. X -TiO2 composite thin film.
[0092] (2) Ti3C2T X The preparation of high concentration slurry is the same as in Example 1.
[0093] (3) The preparation of MAPbI3 single crystal is the same as that in Example 1.
[0094] (4) Ti3C2T X The preparation of the electrode is the same as in Example 1.
[0095] (5) Testing
[0096] Place the sample on the probe station with the upper electrode Figure 1 The Ti3C2T X , the lower electrode is Figure 1 The electrode indicated by 1 in the figure is scanned with voltage on the upper and lower electrodes to obtain the dark current and the photocurrent under 480nm light, as shown in Fig.13 As shown in the figure, by comparing the dark current with the voltage corresponding to the bottom peak of the photocurrent, the open circuit voltage of the device shifts to the right, thus proving that the device has a built-in electric field. When the external voltage is 0V, the time-current curve under periodic light switch illumination is as follows Fig.14 As shown, the device performs very well, as evidenced by its standard square wave shape.
[0097] Example 5
[0098] (1) Ti3C2T X -The preparation of TiO2 composite film is the same as in Example 1.
[0099] (2) Ti3C2T X The preparation of high concentration slurry is the same as in Example 1.
[0100] (3) Preparation of MAPbBrI2 single crystals
[0101] Use a balance to weigh 0.1568 g of MABr and 0.6454 g of PbI2 into a 20 ml sample bottle, add them to 1 ml of DMSO and 1 ml of DMF, respectively, and stir on a 60 °C hot stage for 4 h until the drugs are completely dissolved, to obtain 1.4 mol / l MABr precursor solution and 1.4 mol / l PbI2, respectively. Mix the two solutions, stir on a 60 °C hot stage for 2 h, and obtain 0.7 mol / l MAPbBrI2 solution.
[0102] The composite film prepared in step (1) was placed in a sample bottle containing MAPbBrI2 solution, and the sample bottle was placed on a hot table, the temperature was raised to 85°C and allowed to stand for 4 h, to obtain a MAPbBrI2 single crystal with a thickness of 1 mm grown in situ on the composite film. The film was taken out of the solution and placed in a vacuum oven, and dried at 25°C for 3 h to obtain a Ti3C2T X MAPbBrI2 single crystals grown in situ on -TiO2 composite film.
[0103] (4) Ti3C2T X The preparation of the electrode is the same as in Example 1.
[0104] (5) Testing
[0105] Place the sample on the probe station with the upper electrode Figure 1 The Ti3C2T X , the lower electrode is Figure 1 The electrodes indicated by 4 in the figure are scanned with voltages applied to the upper and lower electrodes to obtain dark current and photocurrent under 480nm illumination, as shown in Fig.15 As shown in the figure, it can be seen that the peak from dark current to photocurrent gradually shifts to the left, so there is a built-in electric field inside the device; when the external voltage is 0V and the wavelength is 480nm, the time-current curve under the periodic optical switch is as follows Fig.16 As shown, a relatively complete square wave is presented, which proves that the device has good performance.
[0106] Example 6
[0107] (1) Ti3C2T X -TiO2 composite film preparation is the same as in Example 1
[0108] (2) Ti3C2T X The preparation of high concentration slurry is the same as in Example 1
[0109] (3) Preparation of MAPbBr2I single crystals:
[0110] Use a balance to weigh 0.2226 g of MAI and 0.5138 g of PbBr2 in a 20 ml sample bottle, add them to 1 ml of DMF and 1 ml of DMSO, respectively, and stir on a 60 °C hot stage for 4 h until the drugs are completely dissolved, to obtain 1.4 mol / l MAI precursor solution and 1.4 mol / l PbBr2, respectively. Mix the two solutions and stir on a 60 °C hot stage for 2 h to obtain 0.7 mol / l MAPbBr2I solution.
[0111] The composite film prepared in step (1) was placed in a sample bottle containing MAPbBr2I solution, and the sample bottle was placed on a hot plate, the temperature was raised to 80°C and allowed to stand for 4 h, to obtain a MAPbBr2I single crystal with a thickness of 1 mm grown in situ on the composite film. The film was taken out of the solution and placed in a vacuum oven, and dried at 25°C for 3 h to obtain a single crystal of MAPbBr2I with a thickness of 1 mm. X MAPbBr2I single crystals grown in situ on TiO2 composite films.
[0112] (4) Ti3C2T X The preparation of the electrode is the same as in Example 1.
[0113] Comparative Example 1
[0114] (1) Ti3C2T X The preparation of the film is the same as in Example 1.
[0115] (2) Ti3C2T X The preparation of high concentration slurry is the same as in Example 1.
[0116] (3) The preparation of MAPbI3 single crystal is the same as that in Example 1.
[0117] (4) Ti3C2T X The preparation of the electrode is the same as in Example 1.
[0118] (5) Testing
[0119] The sample is placed on the probe station, and the upper electrode is Ti3C2T X Electrode, the lower electrode is untreated Ti3C2T X The film is scanned with voltages applied to the upper and lower electrodes to obtain dark current and photocurrent under 480nm light, such as Fig.17 As shown, by comparing the dark current with the voltage corresponding to the bottom peak of the photocurrent, the open circuit voltage of the device does not change. Compared with Example 1, it can be proved that Ti3C2T X After the film is surface oxidized, the TiO2 produced on the surface and the MAPbI3 single crystal generate a built-in electric field, which enables the device to operate self-driven. When the applied voltage is 0V, the time-current curve under periodic optical switch illumination is as follows Fig.18 As shown in the figure, there is an obvious peak on the waveform and the difference between the light current and the dark current is very small. Compared with Example 1, it can be proved that Ti3C2T X The film is treated with surface oxidation to construct a device with better performance.
[0120] It should be noted that the above-mentioned technical contents of the present invention are only for explanation and clarification to enable those skilled in the art to understand the technical essence of the present invention, so the technical contents are not used to limit the substantial protection scope of the present invention. The substantial protection scope of the present invention shall be subject to the claims. Those skilled in the art should know that any modification, equivalent substitution and improvement based on the substantial spirit of the present invention shall be within the substantial protection scope of the present invention.
Claims
1. A perovskite single crystal photodetector based on an electrode / transport layer composite film, comprising an electrode / transport layer composite film located at a lower layer, a perovskite single crystal located at a middle layer, and a Ti3C2T X Electrode; the electrode / transport layer composite film is Ti3C2T X -TiO2 composite film, the perovskite single crystal is in-situ grown on the Ti3C2T X -TiO2 composite film; the Ti3C2T X -TiO2 composite film is made by X The film is oxidized to form a dense layer of TiO2 on the surface, including Ti3C2T X as electrodes, and TiO2 as transport layer.
2. The perovskite single crystal photodetector according to claim 1, characterized in that: The oxidation treatment is natural oxidation treatment, plasma etching treatment or inert gas annealing treatment.
3. The perovskite single crystal photodetector according to claim 1, characterized in that: The perovskite single crystal is MAPbBr Y I 3-Y Single crystal, where 0≤Y≤3.
4. The perovskite single crystal photodetector according to claim 1, characterized in that: The Ti3C2T X -TiO2 composite film thickness is 0.1~0.5mm, the upper layer of Ti3C2T X The electrode thickness is 0.1~0.5 mm, and the perovskite single crystal thickness is 1~10 mm.
5. The method for preparing the perovskite single crystal photodetector according to any one of claims 1 to 4, characterized in that: First, prepare Ti3C2T X -TiO2 composite film, then on Ti3C2T X -TiO2 composite film in situ growth of perovskite single crystals, and then preparation of Ti3C2T on the perovskite single crystals X electrode.
6. The preparation method according to claim 5, characterized in that: The preparation of Ti3C2T X -TiO2 composite films including Ti3C2T X Preparation of aqueous solution, Ti3C2T X The thin film was then oxidized to make Ti3C2T X TiO2 is generated on the film surface to obtain Ti3C2T X -TiO2 composite thin film.
7. The preparation method according to claim 5, characterized in that: Ti3C2T was prepared by evaporation crystallization. X -Perovskite single crystals were grown on the TiO2 composite film.
8. The preparation method according to claim 5, characterized in that: The preparation of Ti3C2T X The electrode is made by centrifugation of Ti3C2T X The aqueous solution is concentrated into a high-concentration slurry, which is then scraped onto the surface of the perovskite layer and dried.
Citation Information
Patent Citations
High-stability perovskite single-crystal photoelectric detector and preparation method and application thereof
CN118524714A